Photoelectric properties of ₂O₃-pGaSe-pInSe cascade heterostructures - Savchyn, V.P.; Stakhira, J.M.; Fiyala, Ya.M.; Furtak, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Cascade heterostructure of nGa₂O₃-pGaSe-pInSe was created, and a corresponding band energy diagram was built. Electrical and photoelectric properties of this structure were investigated. Due to isotype pGaSe-pInSe heterojunction the photosensitivity spectrum of nGa₂O₃-pGaSe-pInSe heterostructure extends up to 1.2 eV in IR range as referred to the photosensitivity spectrum of anisotype nGa₂O₃-pGaSe heterojunction.